Entomopathogenic fungi Fusarium semitectum and Hirsutella thompsonii against eriophyid mite, Calepitrimerus azadirachtae on neem - Navik, O S; Manjunatha, M (Indian Journal of Plant Protection, 2020)
The influence of different concentrations of Fusarium semitectum and Hirsutella thompsonii were evaluated at different stages of Calepitrimerus azadirachtae under laboratory conditions. The fungus, F. semitectum showed maximum mortality of mites 83.3 per cent at adult and 82.2 per cent at an immature stage against the concentration of 2.3 × 109 spores/ml, whereas lowest mortality of 11.8 and 18.0 per cent of adult and immature stages, respectively against the concentration of 2.3×104 spores/ml after six days of spraying. Five concentrations of H. thompsonii was evaluated, among them 4.6 × 108 spores/ml was found superior over all the concentration with 89.8, 86.3 and 83.3 per cent mortality of adults, immatures and eggs, respectively after six days of spraying.